Internships for young scientists at educational institutions in Sweden - A. A. Hrechko; P. R. Ponomarenko; Ie. P. Tertytskyi; V. V. Gololobov (Людина і довкілля: Проблеми неоекології)
The support of young scientists by Ukraine's partner countries during and after the war is key to the restoration and reconstruction of our country. Projects aimed at interaction between young and experienced scientists allow for a synergistic effect that drives the creation of new ideas. Participation in educational projects is the key to gaining new experience, developing new competencies that allow you to comprehensively cover the selected research topics, and look for new non-standard approaches to studying and solving problems. At the beginning of the new academic year, PhD students of the Department of Environmental Monitoring and Protected Areas Management took part in two projects at once. The first project was the Swedish project ‘Competence Aid For Ukraine (CAFU)’, which took place in two stages - remotely and in person with a study tour to Sweden. Associate Professor Anastasiia Klieshch and PhD student Alina Hrechko joined the project. The second project was CAPABLE (Common Academic Practices and Abilities in Learning for Research) of the SI Baltic Sea Neighbourhood programme, which also took place in two stages. Postgraduate students Polina Ponomarenko, Vadym Gololobov, and Ievgen Tertytskyi took part in this project. Teachers of the Karazin Institute of Environmental Sciences also joined both parts of this project. Among the faculty members involved were Professor Andrii Achasov, Associate Professor Ganna Titenko, Associate Professor Svitlana Burchenko, and Lecturer Anna Kot.